Qualitative Insights Into the Impact of Room Pricing and Facilities on Hotel Guest Satisfaction - Wijoyo, Adhistyo; Agil Septian, Bagus; Intiar, Septa; Umar A.J; Bayu A.P (MultiTech Publisher, 2024)
This study examines the subjective effects of room cost and hotel facilities on guest satisfaction. The research investigates how visitors perceive value for money and the impact of different facilities on their entire experience via the use of in-depth interviews, focus groups, observations, and case studies. The results indicate that the degree to which room cost matches the level of services and facilities offered is a key factor in determining visitor happiness. Guests who perceive equitable price in relation to the facilities provided are more inclined to express greater happiness. The inclusion of high-end facilities such as spa services and gourmet cuisine greatly enhances the overall experience for guests, while yet maintaining the importance of critical fundamental utilities. Maximizing visitor satisfaction is crucially dependent on the combination of price strategies with high-quality amenities. The survey further reveals a range of visitor preferences and emphasizes the significance of clear and open communication on price. Suggestions for hotel management entail implementing a well-rounded strategy for pricing and facility offers, utilizing findings from qualitative research to customize services, and remaining aware of rising trends such as sustainability and technology improvements. The research offers useful insights for formulating successful tactics to improve visitor happiness and cultivate long-term loyalty in the hotel business